The Theory of Citrasutras in Indian Painting - Kaur, Kanwaljit (International Journal of Psychosocial Rehabilitation, 2026)
The study of technical treatises in Indian art has piqued the curiosity of many scholars in recent years. This study proposes a critical re-examination of the core Indian notions of painting as detailed in the Sanskrit treatises known as citrasutras, which are considered to be the foundation of Indian painting. It critically explores the various ways in which the books on the theory of Indian painting have been understood and employed in the study of Indian painting, and it proposes a new approach to reading and understanding their notions through an in-depth and systematic investigation of the texts. To the contrary of prior publications on the subject, it is asserted that the planned use of such texts as a standard of critique generally failed because there was an incorrect understanding of what "text" meant for Indian painters. Using the experiences of painters, who are considered to be a valid source of knowledge for our understanding of the citrasutras, Isabella Nardi develops a novel approach to research in this field. She also develops a new conceptual framework for understanding the interconnections between textual sources and the practise of Indian painting. Nardi's work will be of interest to anyone who are interested in Indian painting or Indian art in general because it fills a critical vacuum in Indian academia.